2003
DOI: 10.1111/j.0022-1821.2003.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Actual and Potential Competition: Empirical Evidence From the Pharmaceuticals Market

Abstract: We study actual and potential competition and other factors that determine price paths of brand‐name drugs in the Swedish pharmaceuticals market. The results indicate that the price of the incumbent product is lowered by potential competition, entry of (additional) generics, and the introduction of a so‐called reference‐price system. We also identify a ‘ratchet’ effect, through which price regulation makes entry‐deterring limit‐pricing credible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 22 publications
(13 reference statements)
3
58
0
Order By: Relevance
“…Recently, Ellison and Ellison (2000) have suggested the use of presentation proliferation as a strategic tool of entry deterrence. 6 By increasing the number of presentations available the branded …rm increases the cost to the generic entrant of reproducing the entire product line thereby deterring entry which allows the branded …rm to charge a higher price. (20) and (21).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ellison and Ellison (2000) have suggested the use of presentation proliferation as a strategic tool of entry deterrence. 6 By increasing the number of presentations available the branded …rm increases the cost to the generic entrant of reproducing the entire product line thereby deterring entry which allows the branded …rm to charge a higher price. (20) and (21).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…(20) and (21). Furthermore, the time-invariancy of some of the variables (e.g., N U M SU B_B, N U M P RES, % BREV ) necessitates a RE estimation 6 Another recently popular strategic tool of entry deterrence in the pharmaceutical industry is advertising. Recent analyses include Iizuka (2004) and Scott Morton (2000).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Using instrumental variable method to account for potential endogeneity in the entry decisions of 3 Theoretical literature on reference pricing includes Mestre-Ferrandiz (2003), Brekke et al (2007), Miraldo (2009); empirical literature on reference pricing and substitution reforms includes Aronsson, Bergman, and Rudholm (2001), Pavcnik (2002), Bergman and Rudholm (2003), Buzzelli et al (2006), Puig-Junoy (2007), Kanavos et al (2008), Brekke et al (2009), Granlund (2010), Granlund and Rudholm (2011), Kaiser et al (2014). The survey of studies on the effect of the introduction of reference pricing policies concludes that reference pricing was generally associated with a decrease in the prices of the drugs subject to the policy (Galizzi, Ghislandi, and Miraldo, 2011). parallel traders, they found that competition from parallel imports reduced prices by 12-19%.…”
Section: Introductionmentioning
confidence: 99%
“…The reasoning is two-fold: …rst, innovation incentives should be taken care of in the patent period, so there is no argument for o¤ering rents to brand-name producers after patent expiry. 3 Second, the generic versions are supposed to provide exactly the same health bene…t to consumers as the brand-names, implying that only relative prices should determine the choice of drug, although consumers might have a preference for the brand-name. 4 Consequently, most Western countries impose regulations to control prices and expenditures, and to stimulate competition in the pharmaceutical market.…”
Section: Introductionmentioning
confidence: 99%